Efficacy of 2% lidocaine and 4% articaine in mandibular molars with different pulp diagnoses in the mandibular technique - Adel Alfonso Martínez-Martínez; Evelyn Freyle-Granados; Natalia Senior-Carmona (Universidad de Antioquia, 2018)
Introduction: the inferior alveolar dental nerve block is the method most commonly used by endodontists to achieve local anesthesia during treatments. This study compared the efficacy of two anesthetic solutions: 2% lidocaine with 1:80,000 epinephrine and 4% articaine with 1:100,000 epinephrine in patients with different pulp diagnoses requiring endodontic treatment. Method: an interventional, randomized clinical trial. The sample included 36 patients who were treated at the postgraduate endodontics service at the Universidad de Cartagena in the year 2016. Descriptive statistics and the Chi2 test were used for data analysis, using a limit of 0.05. Results: articaine showed a greater anesthetic effect in vestibular mucosa (88.9%) and tip of tongue (55.6%), compared with lidocaine. The rates of anesthetic success in the lidocaine and articaine groups were 5.6% and 22.2% respectively, but this difference was not statistically significant (p = 0.633). In teeth with normal pulp, the efficacy was 27.3%, and this value considerably decreased in teeth with asymptomatic and symptomatic irreversible pulpitis, with percentages of 5.8% and 12.5% respectively, although this difference was not statistically significant (p = 0.276). Conclusions: no statistically significant differences were found in the anesthetic efficacy of 2% lidocaine and 4% articaine in lower molars with vital pulp. However, articaine showed a better rate of anesthetic success. No statistically significant differences were found when comparing the anesthetic efficacy in molars with normal pulp and molars with inflamed pulp-although the percentage of success in normal pulp was greater than in teeth with irreversible pulpitis.